Argentina's presidential elections - Bollig, B; Sdrigotti, F (Taylor and Francis, 2016)
On 22 November 2015, Mauricio Macri of the Cambiemos (Let’s Change) coalition defeated Daniel Scioli of the Frente para la Victoria (FpV, Victory Front) to become Argentina’s president. Macri is the first president to be elected in the country on a right-wing ticket since the introduction of universal suffrage in 1916. Menem, president from 1989 to 1999, oversaw structural adjustments and massive privatisations, but won office first as a left-wing Peronist with a very different set of pledges. Before then, Argentina’s political right had tended to dispense with elections, with a succession of military coups ushering in conservative or reactionary regimes.